Multiple origins of xenoliths and xenocrysts in the Elephant Moraine 79001 Lithology A olivine‐phyric shergottite. (15th December 2019) - Castle, Nicholas; Kuehl, Ethan; Jones, John; Treiman, Allan
Abstract: Petrographic examination of the xenolith and xenocryst populations in the olivine‐phyric shergottite Elephant Moraine 79001 Lithology A shows more chemical heterogeneity than previously documented. Analyses of olivine grains in 18 megacrysts and in 4 lithic fragments show that these two populations either do not have the same source or that this source is heterogeneous in terms of its time–temperature history. Additionally, among the four lithic fragments analyzed, two are distinctive (1) one contains a major‐element‐equilibrated, euhedral olivine grain and (2) the second contains high‐magnesium pyroxene cores. Furthermore, two populations of ferroan olivine were identified (1) one more ferroan than any other reported in EET 79001 and (2) a slightly less ferroan, unequilibrated olivine, but with a restricted range in Mg#. We have also observed an equilibrated pyroxene grain associated with a zoned olivine megacryst. As a result, we recognize that the xenolith/xenocryst population does not represent the incorporation of a single xeno‐lithology into Lithology A, and propose that it be subdivided into a suite of seven identified lithologies, with the understanding that more are likely to be identified with further study. The abundance of Ca in olivine in the xeno‐lithologies suggests a set of crustal, rather than deep mantle, lithologies. Diffusion rates in olivine suggest that the lithologies were incorporated shortly before rapid cooling of the host magma, preserving preexisting mineral chemical zoning. These mineral chemical zones could have been preserved at lower crustal temperatures for up to 10s of Ka. Trace‐element studies of these distinct populations would be required to test whether they are related by igneous processes from a common source magma.